Investment opportunities for livestock in the north eastern province of Kenya:: A synthesis of existing knowledge - Rakotoarisoa, Manitra A.; Massawe, Stella; Mude, Andrew; Ouma, Robert; Freeman, Ade; Bahiigwa, Godfrey; Karugia, Joseph T. (International Food Policy Research Institute, 2008)
Pastoralism is the dominant livelihood activity in the North Eastern Province (NEP) of Kenya. It is supplemented only by a limited amount of agriculture along the rivers. The province faces various developmental challenges including chronic poverty and food insecurity, low human capital and poor health standards, high vulnerability to climate change, poor infrastructure, insecurity and low crop and livestock productivity. This study synthesises existing knowledge and provides recommendations on livestock investments to increase incomes, create employment and reduce food insecurity in the province. It examines investment opportunities in livestock and presents scenarios that meet the objectives of Kenya’s 2030 vision.